Efficacy and prognostic analysis of venetoclax combined with hypomethylating agents for induction therapy in acute myeloid leukemia: a multi-center real-world study on indication-specific stratification, molecular markers, and hematologic toxicities - Leiming Xia; Mengni Qu; Ling Ge; Yingying Chen; Beibei Zhou; Ting Shi; Yang Liu; Min Ruan; Liang Xia; Jian Hong; Jianjun Li; Wei Qian; et al. (Cancer Cell International)
Abstract The combination of venetoclax and hypomethylating agents (VEN + HMAs) has shown significant progress in treating acute myeloid leukemia (AML), especially for patients not suitable for intensive chemotherapy. However, outcomes for relapsed/refractory AML remain uncertain, and factors influencing VEN + HMAs efficacy are not yet conclusively determined. A retrospective analysis of 181 AML patients treated with VEN + HMAs from October 2020 to January 2024 revealed a CR rate of 39.2%, CR/CRi of 52.5%, ORR of 63.5%, and MRD negativity of 47.3% in patients receiving at least 7 days of treatment. Newly diagnosed patients had better outcomes than the relapsed/refractory group, with CEBPA or IDH1 mutations associated with better CR/CRi rates. Optimization of the treatment regimen with azacitidine may lead to higher CR/CRi rates and MRD negativity. Continuous VEN use over 21 days or maintaining a higher blood concentration may improve outcomes for newly diagnosed AML patients. Hematologic adverse events were common, but there were no significant differences in event rates or recovery times among different VEN treatment durations. VEN + HMAs shows promise in newly diagnosed AML but has limited efficacy in relapsed/refractory AML, indicating a need for more effective strategies. Genetic background, such as CEBPA or IDH1 mutations, influences VEN efficacy, with those mutations showing better CR/CRi rates. Choosing azacitidine for treatment and continuing VEN for over 21 days or at higher concentrations may lead to better responses in AML patients. Trial registration Clinical trial registration: we confirmed that our clinical trial has been officially registered with the Chinese Clinical Trial Registry (ChiCTR) and has been assigned the unique registration number: ChiCTR2400090821.